Enhanced Dye Removal and Antibacterial Efficacy of Copper‐Doped ZnO Nanoparticles on Cellulose Nanofibers - Phuong‐Linh Nguyen; Thi Ngat Tran; Minh Thang Le; Azeem Ullah; Duy‐Nam Phan; Ick‐Soo Kim (Advanced Materials Interfaces)
Abstract Cu‐doped ZnO nanoparticle‐loaded cellulose nanofiber membranes are investigated for their potential photocatalytic and antibacterial properties. ZnO nanoparticles, both undoped and doped with copper, are synthesized by the co‐precipitation process, afterward immobilized onto cellulose nanofibers through the utilization of a dip‐coating technique. Methylene blue (MB) removal is evaluated to inspect the effectiveness of photocatalysts in both UV and Xenon lighting conditions. The morphology and structure of the composite cellulose nanofibers loaded with photocatalysts are then examined using FE‐SEM, TEM, XRD, FTIR, and UV–vis characterizations. Under visible light, the self‐cleaning effects of organic compounds are measured, presenting more than 50% of discoloration for various organic stains. The antibacterial activity is assessed using the Kirby–Bauer disc diffusion method and the plate counting method against the gram‐positive Staphylococcus aureus (S. aureus) and gram‐negative Escherichia coli (E. coli) bacteria. The current study shows that cellulose nanofibers coated with Cu‐doped ZnO nanoparticles exhibited excellent photocatalytic and antibacterial activities.